Intelligent Formation Protocol: An Approach for Enhancing Energy Efficiency and Network Performance in Wireless Sensor Networks - Khudhair, Hayder Ayad (Al-Mustansiriyah Journal of Science, 2025)
Background: To achieve long-term performance and sustainability of the applications and maintain the continuity of the so-called wireless sensor networks (WSNs), especially in extreme conditions, energy problem must be solved Objective: This research is centered on the integration of a routing protocol designed to conserve energy for WSNs, namely the intelligent formation protocol (IFP). Accordingly, the main objective of the protocol is to reduce the overall “energy consumption” and hence maximize the “network lifetime.” Methods: The IFP divides the network into clusters and select cluster head based on two parameters: location and remaining energy. Every cluster head collects data from nodes in its cluster and sends the collected data to the base station. The nodes with higher energy are chosen for cluster head to balance the load and save energy of the nodes. Further, to reduce overall energy consumption, “a multi-hop routing” strategy is used to forward data from CHs to the base station. Results: It is also found from simulation outcomes that IFP has minimal energy consumption than conventional protocols which in turn enhances the network’s lifetime. Conclusions: This protocol improves WSNs performance and therefore appropriate for use in applications such as monitoring of environment and health. Thus, the intended protocols such as IFP concentrating on “energy-saving” enhance the performance and maintenance of WSNs in different practical scenarios.